Pollen morphology of selected species of Ruellioideae (Acanthaceae) in Peninsular Malaysia - Che Amri, Che Nurul Aini; Talip, Noraini; Mohamed, Abdul Latiff; A.J., Amirul-Aiman; M.N, Noor-Syaheera (Malaysian Nature Society, 2017)
The pollen morphology of eight species in subfamily Ruellioideae (Acanthaceae) from Peninsular Malaysia were investigated using light and scanning electron microscopes. Species studied are Hemigraphis alternata (Burm. f) T. Anderson, Hemigraphis reptans (G. Forst.) T. Anderson ex Hemsl., Hygrophila pusilla Blume ex Steud., Ruellia repens L., Ruellia simplex C. Wright, Ruellia tuberosa, L., Sanchezia speciosa Leonard and Strobilanthes crispa T. Anderson. The objective of this study is to assess the taxonomic value of pollen morphological characteristics. Findings in this study have shown some variations in the pollen morphology that can be used in species identification and classification. Pollen description includes pollen classes, shape, apertures, exine thickness and ornamentation. The results have demonstrated that pollen morphology characteristics have taxonomic significance and useful as additional data especially in species identification and classification in subfamily Ruellioideae.